"Liking" as an early and editable draft of long-run affective value. - Peter Dayan (PLoS Biology)
Psychological and neural distinctions between the technical concepts of "liking" and "wanting" pose important problems for motivated choice for goods. Why could we "want" something that we do not "like," or "like" something but be unwilling to exert effort to acquire it? Here, we suggest a framework for answering these questions through the medium of reinforcement learning. We consider "liking" to provide immediate, but preliminary and ultimately cancellable, information about the true, long-run worth of a good. Such initial estimates, viewed through the lens of what is known as potential-based shaping, help solve the temporally complex learning problems faced by animals.